Validation of the beat to beat measurement of blood velocity in the human ascending aorta by a new high temporal resolution Doppler ultrasound spectral analyser. Issue 8 (August 1992) - Coats, A J S; Murphy, C; Conway, J; Sleight, P
Abstract : Objective —To develop and validate a high temporal resolution spectral analysis system for Doppler measurements of blood velocity in the ascending aorta. Design —An observational laboratory and clinical study comparing Doppler velocity-based measurements with fluid collection, electromagnetic flow catheters and probes, and thermodilution. Setting —Tertiary referral cardiology unit and cardiac catheter laboratory. Patients —Patients undergoing routine cardiac catheterisation for ischaemic heart disease, cardiac failure, and primary pulmonary hypertension. Results —There was good agreement between Doppler-derived and electromagnetic cuff or catheter measurements of velocity in an experimental flow rig (SD of differences 4·75% for velocity integral) and in the patients (SD of differences 4% for velocity integral). There was also reasonably good agreement between simultaneous Doppler-derived and thermodilution-estimated cardiac output measurements in patients undergoing cardiac catheterisation (SD of differences 12·6%). Conclusions —This new method of high temporal resolution spectral analysis improves the resolution of rapidly changing blood velocities and may improve the ability to describe blood velocity patterns in the ascending aorta.